Overview of Hybrid MANET-DTN Networking and its Potential for Emergency Response Operations - Raffelsberger, Christian; Hellwagner, Hermann (Electronic Communications of the EASST, 2013)
Communication networks for emergency response operations have to operate in harsh environments. As fixed infrastructures may be unavailable (e.g., they are destroyed or overloaded), mobile ad-hoc networks (MANETs) are a promising solution to establish communication for emergency response operations. However, networks for emergency responses may provide diverse connectivity characteristics which imposes some challenges, especially on routing. Routing protocols need to take transmission errors, node failures and even the partitioning of the network into account. Thus, there is a need for routing algorithms that provide mechanisms from Delay or Disruption Tolerant Networking (DTN) in order to cope with network disruptions but at the same time are as efficient as MANET routing schemes in order to preserve network resources. This paper reviews several hybrid MANET-DTN routing schemes that can be found in the literature. Additionally, the paper evaluates a realistic emergency response scenario and shows that MANET-DTN routing schemes have the potential to improve network performance as the resulting network is diverse in terms of connectivity. In particular, the network provides well-connected regions whereas other parts are only intermittently connected.